Experimental Design of Photo-Fenton Reactions for the Treatment of Car Wash Wastewater Effluents by Response Surface Methodological Analysis. (25th August 2014) - Tony, Maha A.; Bedri, Zeinab
Abstract : Establishing a treatment process for practical and economic disposal of car wash wastewater has become an urgent environmental concern. Photo-Fenton's process as one of the advanced oxidation processes is a potentially useful oxidation process in treating such wastewater. Lab-scale experiments with UV source, coupled with Fenton's reagent, showed that hydrocarbon oil is degradable through such a process. The feasibility of photo-Fenton's process to treat wastewater from a car wash is investigated in the present study. A factorial design based on the response surface methodology was applied to optimize the photo-Fenton oxidation process conditions using chemical oxygen demand (COD) reduction as the target parameter to optimize. The reagent (Fe 2+ and H2 O2 concentration) and pH are used as the controlling factors to be optimized. Maximal COD reduction (91.7%) was achieved when wastewater samples were treated at pH 3.5 in the presence of hydrogen peroxide and iron in amounts of 403.9 and 48.4 mg/L, respectively.